Bionic gliding underwater robots : design, control and implementation /: design, control and implementation. (2022) - (Writer on robotics), Yu, Junzhi; Wu, Zhengxing, 1989-; Wang, Jian, 1993-; Tan, Min, 1962-
No abstract available